2012
DOI: 10.1186/1471-2156-13-90
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a slow-growing line reveals wide genetic variability of carcass and meat quality-related traits

Abstract: BackgroundSlow-growing lines are widely used in France for the production of high quality free-range chickens. While such production is mainly dedicated to the whole carcass market, new prospects are opening up for the development of cuts and processed products. Whether the body composition and meat quality of slow-growing birds can be improved by selection has thus become an important issue. The genetic parameters of growth, body composition and breast meat quality traits were evaluated in relation to behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
27
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 19 publications
(34 reference statements)
11
27
0
4
Order By: Relevance
“…Our results were consistent with the reports of Askit et al (2006) in Ross 308 broiler and Chabault et al (2012) in free range naked-neck chickens. Franco et al (2013) also found a negative correlation (r = -0.38; p < 0.01) between L* and pH was found in Sasso T-44 line and Mos breed chickens.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 83%
See 2 more Smart Citations
“…Our results were consistent with the reports of Askit et al (2006) in Ross 308 broiler and Chabault et al (2012) in free range naked-neck chickens. Franco et al (2013) also found a negative correlation (r = -0.38; p < 0.01) between L* and pH was found in Sasso T-44 line and Mos breed chickens.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 83%
“…This finding corroborates the results of Chabault et al (2012) who reported positive genetic correlation between intramuscular fat content and luminance (r g = 0.42) as well as the shear force (r g =0.57) in free range naked-neck chickens, a slow-growing line selected by the SASSO breeding company. Previous studies had reported positive genetic correlations of abdominal fat weight and abdominal fat percentage with carcass weight in chickens (Deeb and Lamont, 2002;Musa et al, 2006).…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 82%
See 1 more Smart Citation
“…The yields of the thigh-drumstick results of the current study according to the sex are opposite to those of Chabault et al, (2012). They reported in commercial lines that for a given age, the breast and the thigh yields are often higher with females due to their most precocity muscle development in comparison to males.…”
mentioning
confidence: 61%
“…In poultry, high genetic correlations were observed between abdominal fat weight and subcutaneous fat, while there were almost no genetic correlations between abdominal fat weight and intramuscular fat percentage (Zerehdaran et al 2004;Lotfi et al 2011). Selection for reduced abdominal fatness and/or increased breast muscle yield should be effective as both traits were found to be highly heritable and favourably correlated (Ikeobi et al 2002;Jennen et al 2004;Chabault et al 2012). …”
Section: Introductionmentioning
confidence: 99%